Correlation between acylcarnitine/free carnitine ratio and cardiopulmonary exercise test parameters in patients with incident dialysis - Ito, Wataru; Uchiyama, Kiyotaka; Mitsuno, Ryunosuke; Sugita, Erina; Nakayama, Takashin; Ryuzaki, Toshinobu; Takahashi, Rina; Katsumata, Yoshinori; Hayashi, Kaori; Kanda, Takeshi; Washida, Naoki; Sato, Kazuki; et al. (Frontiers in Physiology, 2023)
Objective: Diminished physical capacity is common and progressive in patients undergoing dialysis, who are also prone to deficiency in carnitine, which plays a pivotal role in maintaining skeletal muscle and cardiac function. The present study aimed to evaluate the association of carnitine profile with exercise parameters in patients with incident dialysis. Design and Methods: This was a single-center cross-sectional study including 87 consecutive patients aged 20–90 years who were initiated on dialysis in Keio University Hospital between December 2019 and December 2022 and fulfilled the eligibility criteria. Exercise parameters were evaluated via cardiopulmonary testing (CPX) using the electronically braked STRENGTH ERGO 8 ergometer, whereas the carnitine profile was assessed by determining serum free carnitine (FC), acylcarnitine (AC) levels and AC/FC ratio. Results: The mean cohort age was 62.1 ± 15.2 years, with male and hemodialysis predominance (70% and 73%, respectively). AC/FC was 0.46 ± 0.15, and CPX revealed peak oxygen consumption (VO2) of 13.9 ± 3.7 (mL/kg/min) with percent-predicted peak VO2 of 53.6% ± 14.7% and minute ventilation (VE)/carbon dioxide output (VCO2) slope of 35.1 ± 8.0. Fully-adjusted multivariate linear regression analysis showed that AC/FC was significantly associated with decreased peak VO2 (β, −5.43 [95% confidence interval (CI), −10.15–−0.70]) and percent-predicted peak VO2 (β, −19.98 [95% CI, −38.43–−1.52]) and with increased VE/VCO2 slope (β, 13.76 [95% CI, 3.78–23.75]); FC and AC did not exhibit similar associations with these parameters. Moreover, only AC/FC was associated with a decreased peak work rate (WR), percent-predicted WR, anaerobic threshold, delta VO2/delta WR, and chronotropic index. Conclusion: In patients on incident dialysis, exercise parameters, including those related to both skeletal muscle and cardiac function, were strongly associated with AC/FC, a marker of carnitine deficiency indicating altered fatty acid metabolism. Further studies are warranted to determine whether carnitine supplementation can improve exercise capacity in patients on incident dialysis.